The role of parathyroid autotransplantation for hypoparathyroidism following total thyroidectomy with bilateral central neck dissection - Wang, Peisong; Xue, Haowen; Zhu, Xuemei; Xue, Shuai (Frontiers in Endocrinology, 2024)
Background:Hypoparathyroidism is the most common complication for patients who undergo total thyroidectomy (TT) with bilateral central lymph node dissection (BCLND). The objective of this retrospective study was to investigate the relationship between parathyroid autotransplantation (PA) and postoperative hypoparathyroidism.Four hundred and sixty-five patients with papillary thyroid carcinoma (PTC) who underwent TT with BCLND (including prophylactic and therapeutic BCLND) by the same surgeon were enrolled in this retrospective study. They were divided into five groups based on the number of PAs. Group 0 was defined as no PA, while Group 1, 2, 3, and 4 were considered as 1, 2, 3, and 4 PAs during TT with BCLND, respectively.:Transient and permanent hypoparathyroidism occurred in 83 (17.8%) and 2 (0.4%) patients who underwent TT and BCLND, respectively. The incidence of transient hypoparathyroidism increased gradually with an increase in the number of PAs. Compared with the previous group, Groups 2 and 3 had significantly more cases of transient hypoparathyroidism (p=0.03 and p=0.04, respectively). All cases of permanent hypoparathyroidism occurred in the patients without PA. Compared with Group 0, there were more removed central lymph nodes (RCLNs) in patients with one PA. Furthermore, Group 2 had more metastatic central lymph nodes(MCLNs) and RCLNs than Group 1.The number of PAs was the only identified risk factor for transient hypoparathyroidism after the multivariate logistic regression analysis. The median parathyroid hormone level recovered to the normal range within 1 month after surgery. Conclusion:With an increasing number of PAs, the possibility of transient hypoparathyroidism also increases in patients with PTC who undergo TT and BCLND. Considering the rapid recovery of transient hypoparathyroidism in 1 month, two PAs during TT and BCLND could be a good choice, leading to an increase in the central lymph node yield and no permanent hypoparathyroidism. However, this conclusion should be validated in future multicenter prospective studies.